Understanding Profit Accounting Practices by Binthe Biluhuta Sellers - Paputungan, Vindi; Mohamad, Roni; Rahmatia, Rahmatia; Thalib, Mohamad Anwar (Jurusan Akuntansi Fakultas Ekonomi Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2025)
Purpose: This study aims to understand profit accounting practices by binthe biluhuta sellers based on local cultural values.Method: This study uses an Islamic paradigm with an Islamic ethnomethodological approach. There are five data analysis stages: charity, knowledge, faith, revelation information, and courtesy.Results: The study results show that binthe biluhuta sellers practice value-sharing-based profit accounting, among others. This value is reflected through the use of profits not only to fulfill personal interests but profits from selling binthe biluhuta are also used to help each other. In Gorontalo's Islamic culture, elders often internalize the value of sharing among others through the expression